(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Antenatal diagnosis of congenital CMV infection is based on the detection of primary CMV infection in a pregnant woman, reactivation of latent or superinfection with a new strain of CMV (B). The standard of examination of a pregnant woman is the determination of specific antibodies of Ig M and Ig G classes, Ig G avidity in serum by enzyme-linked immunosorbent assay (hereinafter referred to as ELISA) or immunochemiluminescence assay (hereinafter referred to as CLIA), performed initially at the diagnosis of pregnancy [19,20,21,22].